(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Russian policy, since the dissolution of the Soviet Union, has been based on an attempt to build security and economic strategies with the countries that became independent from it, with the aim of protecting its regional surroundings, especially in light of Western policies that work to contain and encircle Russia and prevent it from winning allies. Therefore, Russia worked to build regional blocs and groupings with neighboring countries, including security groupings to enhance security in the region, such as the Collective Security Treaty, and blocs with the aim of resolving and controlling border disputes such as the Shanghai Five, which later turned into a regional economic bloc, and Russia is still working to try to attract regional countries Whether politically or economically, with the aim of developing its role in the region, it formed the Eurasian Economic Union, which aims to bring about regional economic integration. Perhaps the Russian dimensions behind this union lie in the Russian security and economic visions in protecting its interests in the Eurasian region.